Exploring Sustainable Tourism Practices: A Qualitative Study of the Local Community Perspective in Amadeo, Cavite - Vega, Justine Erika Mia (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study explored sustainable tourism practices in Amadeo, Cavite from the perspective of the local community. It aimed to identify the practices implemented in the municipality, determine their perceived environmental, economic, and socio-cultural effects, examine their contribution to quality of life, and identify the benefits and challenges experienced by residents. The study was anchored on Sustainable Tourism Development Theory and the triple bottom-line framework, emphasizing the balance among environmental protection, economic development, and socio-cultural preservation. A qualitative research design was used, with data gathered through a validated structured interview guide. Four purposively selected key informants participated in the study: a tourism officer, a coffee farm owner, a barangay council member, and a homestay operator, all of whom had direct knowledge of sustainable tourism initiatives in Amadeo. Findings revealed that sustainable tourism strengthened environmental awareness through waste management, tree planting, organic farming, clean-up activities, and environmental education. It also promoted cultural pride, local traditions, coffee-based identity, livelihood opportunities, entrepreneurship, and community participation in tourism governance. However, challenges were also identified, including waste accumulation, damage to farms during peak tourism periods, rising prices, uneven access to benefits, infrastructure strain, limited awareness, and possible commercialization of traditions. The study concludes that sustainable tourism in Amadeo contributes to community development but requires inclusive planning, stronger governance, improved infrastructure, and continuous education. The study is aligned with SDG 8, SDG 11, SDG 12, SDG 13, SDG 15, and SDG 17. Its sustainability impact lies in supporting environmental protection, cultural preservation, local economic resilience, participatory governance, and community-based tourism development.
Keywords: Community Participation; Cultural Preservation; Economic Opportunities; Environmental Awareness; Local Governance; Sustainable Tourism; Tourism Development; Waste Management